2017
DOI: 10.1126/sciadv.1600815
|View full text |Cite
|
Sign up to set email alerts
|

The tropical lapse rate steepened during the Last Glacial Maximum

Abstract: A new temperature record from East Africa demonstrates that the tropical lapse rate steepened during the last ice age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
120
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 58 publications
13
120
2
Order By: Relevance
“…During the Late Glacial (pre‐LGM and LGM) a downward shift of the montane forest, characterized by the development a sub‐alpine vegetation associated with components of afro‐alpine grassland at our site is consistent with a colder climate than generally recorded in tropical East Africa today (Gasse, Chalié, Vincens, Williams, & Williamson, ; Loomis et al., ). On the other hand, hydrological changes reveal a more complex pattern characterized by generally dry conditions interrupted by more humid periods prior to the LGM (Tierney, Russell, & Huang, ).…”
Section: Discussionsupporting
confidence: 80%
“…During the Late Glacial (pre‐LGM and LGM) a downward shift of the montane forest, characterized by the development a sub‐alpine vegetation associated with components of afro‐alpine grassland at our site is consistent with a colder climate than generally recorded in tropical East Africa today (Gasse, Chalié, Vincens, Williams, & Williamson, ; Loomis et al., ). On the other hand, hydrological changes reveal a more complex pattern characterized by generally dry conditions interrupted by more humid periods prior to the LGM (Tierney, Russell, & Huang, ).…”
Section: Discussionsupporting
confidence: 80%
“…LGM simulations typically feature a global annual cooling of 4 to 6 • C relative to pre-industrial; e.g., Braconnot et al, 2007) -Loomis et al (2017 showed that the tropical atmospheric lapse rate may have increased from about 5.8 • C km −1 in the modern climate, to 6.7 • C km −1 at the LGM. The elevation difference in the interior of the Laurentide ice sheet is around 200 m between the T85 and T21 cases (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If a direct transfer function relating temperature to GDGTs is available for a given site or region, it can be specified as the parameter β in function lake_sensor_gdgt.py. For the purposes of demonstration, a number of potential calibration values for β are listed based on values used by Powers et al () and Loomis et al ().The temperature‐ T E X 86 relationship is inverted to yield a forward estimate of the proxy measurement: TEX86=βLST, TEX86=false(LST+14.0false)false/55.0,0.3emfalse[Powers0.3emet0.3emal.,2011false] TEX86=false(LST+10.92false)false/54.88,0.3emfalse[Loomis0.3emet0.3emal.,2017false] where L S T is lake surface temperature, and β is the proxy/temperature transfer function or calibration set by the user.Recent calibration studies have developed calibrations for brGDGTs in lakes with mean annual temperatures based upon a version of the MBT index which use only 5‐methyl isomers ( MBT5ME). These compounds in particular have been shown to correlate with MAAT (e.g., De Jonge et al, ; Russell et al, ).…”
Section: Proxy System Modeling For Lacustrine Archives Of Past Climatementioning
confidence: 99%
“…If a direct transfer function relating temperature to GDGTs is available for a given site or region, it can be specified as the parameter β in function lake_sensor_gdgt.py. For the purposes of demonstration, a number of potential calibration values for β are listed based on values used by Powers et al () and Loomis et al ().…”
Section: Proxy System Modeling For Lacustrine Archives Of Past Climatementioning
confidence: 99%
See 1 more Smart Citation